Teologi Berhala Berbasis Keluaran 32:1-14 - Anton Sitorus; Iwan Setiawan Tarigan (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article aims to discuss the life of faith of the Israelites as God's chosen people, whether they were loyal to God or to Baal, especially on the journey to the promised land. The Israelites undertook a long and challenging journey. They were ordered by the prophet Moses to be free from Egypt and after Moses' death he was replaced by Joshua, the Israelis lived their lives in the desert for about 40 years, finally reaching the promised land promised by God. For 40 years in the desert, they got food in the form of manna and quail. They also experienced various tests and trials including rebellion and disbelief in God's guiding hand. The Israelites were known as an impatient nation. For example, when Moses was on Mount Sinai when God gave His law to Moses and Moses took too long to come down from the mountain. The Israelites there could not wait patiently because they were afraid of death and starvation because there was no one to lead. They talked to Harun to make a golden calf statue, which was considered to have power and was believed to be a substitute for God to continue their journey. They made a statue of a golden calf because Moses had not come down from Mount Sinai and was thought to be dead. The impatient attitude of the Israelites finally took a shortcut by making a golden calf that was considered to be able to replace God's position. Of course this made God angry because it had violated the 2nd commandment, namely "do not make for yourself any idol".